THE AGRIBUSINESS SYSTEM OF COOPERATION BUSINESS GROUP “SEJAHTERA” SIMPANG TIGA VILLAGE ENOK SUB DISTRICT INDRAGIRI HILIR RIAU PROVINCE - Kartini Kazid; Zulkarnaini '; Hendrik ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The study was conducted on 18 February - 28 February 2015 in the village of Simpang Tiga Enok Sub District. The purpose of this study is to determine the development of their respective businesses in KUB Sejahtera, to determine the application of existing agribusiness system in KUB Sejahtera and pinpoint the role of KUB Sejahtera against agribusiness system activity. The Determination of respondents conducted by purposive sampling that people who become members of the KUB who served as chairman of the KUB, deputy chairman of the KUB, KUB Secretary, Treasurer KUB and each head of each line of business. Based on the results of research in KUB Sejahtera, the result of shrip fishing in 2013 as much as 10621.8 kg increased to 17576.7 kg in 2014. As for fishing of crab in the year 2013 as many as 5165.7 Kg slightly decreased to 5081.85 Kg in 2014. Cultivation only in 2015 alone that in January-April as many as 635.6 Kg. Processing business in 2013 as much as 96 kg and increased production in 2014 as much as 115 kg. Application of agribusiness system in KUB Sejahtera is already well on arrest effort, cultivation and marketing while processing its application has not been going well. The role of KUB Sejahtera toward agribusiness system activity is as a facilitator of activities in four businesses in KUB Sejahtera.Keywords : System, Agribusiness, KUB, Sejahtera